Effect of caffeine ingestion on 200 meter running performance Efeito da ingestão de cafeína no desempenho em corrida de 200 metros rasos - Cardoso T.E.* (2013)
The aim of this study was to investigate the influence of caffeine ingestion on 200 meters performance (200 m). Seventeen physical education students (21.5 ± 2.15 years; 175.9 ± 5.5 cm; 74.1 ± 10.04 kg) performed on two different days two performances of 200 m. One hour before the performance the participants ingested a gelatin capsule containing either caffeine (6 mg.kg-1) or placebo in a randomized double-blinded manner. Were analyzed the end time of the 200 m race and blood lactate ([La]; rest, pre-warm-up and post-test) Caffeine intake decreased the time to overcome 200 m race compared to placebo intake (27.398 ± 1.626 and 27.596 ± 1.714 s, respectively) and increased blood lactate concentration [La] pre-warm-up (1.236 ± 0.497; 1.064 ± 0.330 mM, respectively) without modification in [La] peak. Thus, we conclude that caffeine intake exert an ergogenic effect on anaerobic performance, however analyzing the [La] peak, this improvement does not seem to be related to increased glycolytic flux.